Rational Design of Transition Metal‐Based Materials for Highly Efficient Electrocatalysis. Issue 1 (27th September 2018) - Dou, Shuo; Wang, Xin; Wang, Shuangyin
Abstract: Electrocatalysts play critical roles in the renewable electrochemical energy storage and conversion systems. The conventional noble metal‐based electrocatalysts cannot satisfy the demand of large‐scale manufacturing due to their high‐price and scarce reserves in the earth. Therefore, rational designing of transition metal‐based materials to endow high activity, selectivity, stability, and low cost has been regarded as an alternative of noble metal‐based materials. Here, recent effective and facile strategies to rationally design transition metal‐based electrocatalysts, such as increasing the number active sties, improving the utilization of active sites (atomic‐scale catalysts), modulating the electron configurations, as well as controlling the lattice facets, for oxygen reduction reaction, oxygen evolution reaction, hydrogen evolution reaction, and CO2 reduction reaction, are summarized. It is believed that based on the understanding of fundamental design principles, well‐designed non‐noble metal and even metal free electrocatalysts would further make the electrochemical energy conversion and storage great promise in the future. Abstract : Transition metal‐based electrocatalysts are regarded as promising candidates to replace the use of noble metal‐based materials as a core part in renewable electrochemical energy storage and conversion systems. Rational designing of the electrocatalysts with more active sites, modulated electron configuration, controlled lattice facets, etc., is proved to be an efficient strategy to obtain high activities, selectivity, and stability.